Af ec tos l l lacu nar e s: um estudo acerca da poética do arquivo e do impulso anarquivístico - Gabriela Lopes Drumond de Sa (2017)
This research starts at an archive and goes back to it. Thereforeit proposes a theoretical and practical investigation over the possibilitiesof new ways of investment for the contemporary artist who works witharchival material. By the use of concepts discussed by authors such asWalter Benjamin, Maurício Lissovsky, Paul Ricoer, Lucia Castello Branco,André Rouillé, Georges Didi-Huberman and Maurice Blanchot, we will turn ourselves to the relationships between archive, memory, oblivion, history and fiction, in order to reflect with a critical review on the documental power and probatory value of archives and of images as such. For that, throughout this dissertation, we will evoke works of contemporary artists such as Walid Raad, Susan Hiller, Mary Kelly, Zoe Leonard, Cristina de Middel etc, and also my own artworks. Through the figure of the gap which is essential for understanding a poetic dimension of the archive we are willing to research the potentialities of the concept of the anarchival impulse that was used for the first time by Hal Foster (2004) and can be set against the archive drive and the archival impulse proposed by Jacques Derrida (2001). The intention is, thus, to investigate the affects (pathos) that those images and documents recall and the gestures that they urge when we are working within their gaps. At the end, I will turn to the propositions made by Blanchot around the two versions of the imaginary in order to investigate the relationship between what is visible and non-visible; past and future; memory and oblivion; reality and fiction, seeking for the power of a poetic mergebetween the fabulation of the artistic gesture and the reality within the archive.